Peri-procedural, 30-day and 1 year-outcomes in chronic dialysis patients undergoing transcatheter aortic valve implantation. (3rd October 2022) - Albuquerque, F; Lima, R; Campante Teles, R; Gomes, D; Lopes, P; Felix Oliveira, A; Goncalves, M; Brito, J; Raposo, L; Leal, S; Mesquita Gabriel, H; De Araujo Goncalves, P; et al.
Abstract: Background: Patients on chronic dialysis (CD) due to end-stage renal disease (ESRD) with symptomatic severe aortic stenosis eligible for transcatheter aortic valve implantation (TAVI) were excluded from randomized clinical trials. Our study aimed to investigate the outcomes of patients with chronic dialysis who underwent TAVI. Methods: Single center analysis on prospectively collected data of all consecutive patients who underwent TAVI between January 2011 and December 2020 according to baseline renal function: chronic dialysis group (CD) and control group (CTRL). Procedural, 30-day and 1-year outcomes were assessed. Outcomes were defined in accordance with the VARC-3 criteria. Results: A total of 875 patients underwent TAVI during the study period, of whom 22 (2.5%) were on chronic dialysis. Patients on CD were younger (median age 80 years, [IQR 73–84] vs 84 years, [IQR 80–87]; p<0.001), more likely to be men [365/863 (42.8%) vs 18/22 (81.8%); p<0.001] and more likely to have peripheral vascular disease [41/853 (4.8%) vs 7/22 (31.8%); p=0.031] and lower body mass index (median 24.1 kg/m 2, [IQR 21.5–26.5] vs 26.3 kg/m 2, [IQR 23.7–29.3]). Short-term major or life-threatening bleeding were significantly higher in CD patients (odds ratio [95% confidential interval]: 3.67 [1.50–8.96], p 0.005). In contrast, no differences were found regarding rates of vascular complications requiring intervention (OR [95% CI]: 1.35 [0.31–5.90], p=0.662), permanent pacemaker implantation (OR [95% CI]: 0.87 [0.25–2.98], p=1.000) or stroke (OR [95% CI]: 1.51 [0.20–11.64], p=0.504). Importantly, dialysis patients had significantly higher rates of in-hospital, 30-day and 1-year mortality rates (13.6 vs 2.1%, p<0.001; 18.9% vs 2.9, p<0.001 and 26.4% vs 10.7%, p<0.001, respectively). On multivariate analysis, after adjusting for age, gender, relevant co-morbidities, and procedure-related complications, CD remained independently associated with mortality at 1-year. Survival curves during follow up are presented in Figure 1. Conclusions: Chronic dialysis patients submitted to TAVI had significantly higher rates of short-term life threatening and/or major bleeding, short-term and long-term mortality. Careful selection of patients who would benefit from TAVI among patients with ERDS requiring dialysis is necessary to prevent high rates of postprocedural complications and improve outcomes of this high-risk population. Funding Acknowledgement: Type of funding sources: None.